Selection of continuous improvement (CI) tools for improvement of organisational culture and performance towards world class manufacturing. (1st January 2013) - Muthukumar, N.; Tamizhjyothi, K.; Nachiappan, R.M.; Anatharaman, N.
World class manufacturing (WCM) has attracted the attention of industries due to competitive and unstable global market conditions. This article describes the basis for world class manufacturing (WCM) and discusses the role of culture and performance measurement with nine culture and performance elements called culture and performance elements (CPE). This article focuses on selecting the best CI tools based on factor analysis and analytical hierarchy process (AHP), and examining their relationship with CPE. The proposed three best CI tools are applied in a manufacturing environment to achieve world class culture and performance in a short span of time.